Incremental shuttle walking test for calf muscle oxygenation assessment in peripheral arterial disease: a cross-sectional study - Patrícia Paulino Geisel; Isabella de Oliveira Nascimento; Marina Mendonça Gonçalves Machado; Raimundo Lucas Gomes Mateus dos Santos; Bruno Rafael Nézio Gomes; Gisela Maria Pontes Przybysz; Isabel de Figueiredo Magalhães Pereira; Danielle Aparecida Gomes Pereira (Scientific Reports)
Abstract People with peripheral arterial disease (PAD) and intermittent claudication (IC) experience impaired walking due to an imbalance between muscle oxygen supply and demand during exercise. Studies with near-infrared spectroscopy (NIRS) during treadmill tests reveal notable tissue deoxygenation with slow recovery. This cross-sectional study aimed to compare behavior of calf muscle oxygenation during the incremental shuttle walking test (ISWT) with a continuous treadmill test (3.2 km/h, 10% incline) and to correlate NIRS results between tests in PAD patients. Sixty individuals with IC, 37 men (61.7%), mean age 66.25 ± 10.35 years participated in the study. Both tests were performed on the same day with a 30-minute rest, in randomized order. NIRS-derived calf muscle tissue oxygenation variables were measured at rest and during exercise. Typical PAD tissue oxygenation patterns were observed in both tests, with significant differences (p < 0.05) in oxygenation values during exercise for the variables delta of tissue oxygen saturation (ΔStO2) and reoxygenation rates. All tissue oxygenation variables analyzed, except reoxygenation rate, showed a significant and directly proportional correlation between the two tests. These results suggest that NIRS during ISWT could be a viable method for assessing tissue oxygenation in PAD.